ADAPTATION OF THE HUMAN ORGANISM TO THE CONDITIONS OF CLIMATE CHANGE - Qallieva Rayxan Torebaevna; Sipatdinova Gulnaz Asamatdinovna (Journals Park Publishing, 2024)
The article Adaptation of the human organism to the conditions of climate change. Among the ecological factors, various diseases appear in the human body as a result of the transfer of pollutant compounds to food products through air pollution, water resource pollution, and soil pollution. According to scientific sources, the incidence is high in Nukus district.
Keywords: factor, disease, pollution, organism, external environment.